Dissociable mechanisms of cognitive control in human prefrontal cortex - GARAVAN, HUGH PATRICK (The American Physiological Society, 2007)
Intelligent behavior depends on the ability to suppress inappropriate actions and resolve interference between competing responses. Recent clinical and neuroimaging evidence has demonstrated the involvement of prefrontal, parietal, and premotor areas during behaviors that emphasize conflict and inhibition. It remains unclear, however, whether discrete subregions within this network are crucial for overseeing more specific inhibitory demands. Here we probed the functional specialization of human prefrontal cortex by combining repetitive transcranial magnetic stimulation (rTMS) with integrated behavioral measures of response inhibition (stop-signal task) and response competition (flanker task). Participants undertook a combined stop-signal/flanker task after rTMS of the inferior frontal gyrus (IFG) or dorsal premotor cortex (dPM) in each hemisphere. Stimulation of the right IFG impaired stop-signal inhibition under conditions of heightened response competition but did not influence the ability to suppress a competing response. In contrast, stimulation of the right dPM facilitated execution but had no effect on inhibition. Neither of these results was observed during rTMS of corresponding left-hemisphere regions. Overall, our findings are consistent with existing evidence that the right IFG is crucial for inhibitory control. The observed double dissociation of neurodisruptive effects between the right IFG and right dPM further implies that response inhibition and execution rely on distinct neural processes despite activating a common cortical network.
PUBLISHED
Keywords: Psychology